2008
DOI: 10.1080/01446190802017706
|View full text |Cite
|
Sign up to set email alerts
|

Construction linkages in a developing economy: the case of Sri Lanka

Abstract: The importance of the construction industry stems from its strong linkages with other sectors of the economy. Despite the extensive research on input-output analysis and sectoral linkages of construction, a gap is found in the literature dealing with developing economies. The objective is to study the construction linkages in a developing economy using input-output tables compiled since the 1970s in Sri Lanka. Results show that the share of construction in gross national product and national income is lower in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
(22 reference statements)
1
12
0
Order By: Relevance
“…Bon (1992) introduced the inverted U curve to depict the evolving role of the construction industry in the economy as it develops from LDC to NIC to AIC. Rameezdeen and Ramachandra (2008) discovered that the contribution of construction to gross national product (GNP) and national income (NI) was lower in Sri Lanka than in developed countries, which would serve as an example of the "Bon curve". Using data from 1973 to 2002, Gundes (2011) also found a strong correlation between construction activities and economic development in Turkey although the GNP share of the construction industry had been declining since the 1990s.…”
Section: Share Of the Construction Industry In The Economymentioning
confidence: 98%
“…Bon (1992) introduced the inverted U curve to depict the evolving role of the construction industry in the economy as it develops from LDC to NIC to AIC. Rameezdeen and Ramachandra (2008) discovered that the contribution of construction to gross national product (GNP) and national income (NI) was lower in Sri Lanka than in developed countries, which would serve as an example of the "Bon curve". Using data from 1973 to 2002, Gundes (2011) also found a strong correlation between construction activities and economic development in Turkey although the GNP share of the construction industry had been declining since the 1990s.…”
Section: Share Of the Construction Industry In The Economymentioning
confidence: 98%
“…Also, Zheng et al (2012) reported that property price and construction industry's output are positive related. Empirical evidence has established that a strong positive relationship exist between the construction industry and the economy (Rameezdeen and Ramachandra, 2008;Dang and Low, 2011). It is therefore reasonable to infer that the real estate sector plays a critical role in the economy.…”
Section: Introductionmentioning
confidence: 99%
“…Construction has strong linkages with many other economic activities and whatever happens to the industry will influence other industries and ultimately the general economy (Ball, 1988; Bon et al , 1999; Pietroforte and Bon, 1995; Bon, 2000; Pietroforte et al , 2000; Rameezdeen and Ramachandra, 2008).…”
Section: Introductionmentioning
confidence: 99%